A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages which an expert advisory body would recommend a number of suitable candidates from which the hospital authority would make the final choice. V CLINICS AND OTHER LOCAL SERVICES Services required The National Health Service must include arrangements for home nursing, midwifery and health visiting; it must also include the local clinics and similar services which are now provided for maternity and child welfare and other special purposes, or which may have to be provided in the future. In England and Wales, the joint authority will have the duty of including all these local services in their general plan for the area and ensuring that they are properly related to each other and to the other parts of the National Service and are arranged in the right way and in the right place to meet the area's needs. The plan, as approved by the Minister, will finally determine in each area which of the services are to be provided and maintained by the county and county borough councils and which by the joint authority. Different arrangements will be necessary in Scotland, but the general principle in both countries will be that all the local services which belong to the sphere of general health care will rest with the major local authority, while those which belong to the hospital and consultant sphere will rest with the new joint authority. Importance of work in clinics As time goes on and the new scheme gets into its stride, there will be room for experiment and innovations in the way in which these various local services are provided. In particular, there will be opportunities for associating the family doctor more closely with the work of special clinics — e.g., child welfare centres. But, whatever developments there may be in the clinics and other locally provided services, the introduction of the new service will not mean that any existing facilities are abandoned, but rather that they will be increased and strengthened to meet the wider objects in view. The way in which the Government's proposals, based on these principles, will affect the various services is described below. Maternity and child welfare services The arrangement of lying-in accommodation in hospital or maternity home (indeed all the institutional provision for maternity, both for normal and for complicated cases) will become part of the reorganised hospital and consultant services and will be the responsibility of the new joint authority. The ordinary functions of the maternity and 18 36/H24/41